2022
DOI: 10.1002/advs.202204885
|View full text |Cite
|
Sign up to set email alerts
|

RNA 5‐Methylcytosine Modification Regulates Vegetative Development Associated with H3K27 Trimethylation in Arabidopsis

Abstract: Methylating RNA post-transcriptionally is emerging as a significant mechanism of gene regulation in eukaryotes. The crosstalk between RNA methylation and histone modification is critical for chromatin state and gene expression in mammals. However, it is not well understood mechanistically in plants. Here, the authors report a genome-wide correlation between RNA 5-cytosine methylation (m 5 C) and histone 3 lysine27 trimethylation (H3K27me3) in Arabidopsis. The plant-specific Polycomb group (PcG) protein EMBRYON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The dynamic modulation of pseudouridine under changing conditions further emphasized the reversibility and dynamic nature of RNA modifications and the epitranscriptome (Begik et al., 2021; Schwartz et al., 2014; Sun et al., 2019). The crosstalk and interplays between epigenetics and epitranscriptomics were also suggested and discussed recently (Kan et al., 2022; Xu & Shen, 2022; Zhang, Guo et al., 2023). These novel findings provide new insights into plant developmental biology and plant–environment interactions.…”
Section: Introductionmentioning
confidence: 85%
“…The dynamic modulation of pseudouridine under changing conditions further emphasized the reversibility and dynamic nature of RNA modifications and the epitranscriptome (Begik et al., 2021; Schwartz et al., 2014; Sun et al., 2019). The crosstalk and interplays between epigenetics and epitranscriptomics were also suggested and discussed recently (Kan et al., 2022; Xu & Shen, 2022; Zhang, Guo et al., 2023). These novel findings provide new insights into plant developmental biology and plant–environment interactions.…”
Section: Introductionmentioning
confidence: 85%
“…ZmBELL10‐myc transgenic plants were used for ChIP assays as previously described (Xu et al ., 2018; Zhang et al ., 2022). The chromatin complexes were incubated with anti‐MYC antibody (1 : 10 000 (v/v); Abcam, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…434 In addition, mRNA modification by m5C plays a key role in transcription, RNA stability, and translational regulation. 435 Evaluation of the modification patterns of 530 tumoral samples in clear cell renal cell carcinoma (ccRCC) revealed that m5C methylation benefits the regulation of ccRCC immune infiltration. 436 Moreover, mRNA-based synthesis of therapeutic proteins confers distinct advantages, such as highly controlled translational kinetics and a minimized risk of insertional mutagenesis.…”
Section: Chemical Modifications On Mrnamentioning
confidence: 99%
“…The use of the pseudouridine and m5C-modified RALA mRNA nanocomplex has been shown to enhance the potency of cytolytic T cell responses . In addition, mRNA modification by m5C plays a key role in transcription, RNA stability, and translational regulation . Evaluation of the modification patterns of 530 tumoral samples in clear cell renal cell carcinoma (ccRCC) revealed that m5C methylation benefits the regulation of ccRCC immune infiltration …”
Section: Chemical Modifications On Rna Molecules In Preclinical Researchmentioning
confidence: 99%